Sustainability Communication and the Concept of Sustainability: An Analysis in the Case of the Turkish Bank Sector Website and Sustainability Reports - Demirci, Kenan (Marmara Univ, Fac Communication, 2022)
The concept of sustainability focuses on specific solutions to environmental, social, and economic problems, similar to corporate social responsibility (CSR). However, the concept of sustainability can be described as an expanded version of CSR in many respects. Basic meanings of sustainability can indicate that companies must redefine their relationships with all activities and society to promote sustainable development. This broad meaning of sustainability requires effective use of communication opportunities in social life. Successfully communicating across many arenas will certainly lay the foundations for more a thoroughly sustainable process. For this reason, sustainability communication should be considered an important concept. This study aimed to analyse the way that the concept of sustainability is included in websites and sustainability reports, which are two important tools of sustainability communication. In this context, the websites and sustainability reports of five private and public banks operating in Turkey were analysed through a qualitative analysis within the scope of the case study technique. As a result, it was revealed that banks have taken important steps in defining the concept of sustainability and making efforts regarding this concept, but the banks are somewhat inadequate in developing tools that will include social dynamics in the process.
Keywords: Sustainability; sustainability communication; websites; sustainability reports; banks and sustainability